2022
DOI: 10.1038/s41467-022-30260-4
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-dense dislocations stabilized in high entropy oxide ceramics

Abstract: Dislocations are commonly present and important in metals but their effects have not been fully recognized in oxide ceramics. The large strain energy raised by the rigid ionic/covalent bonding in oxide ceramics leads to dislocations with low density (∼106 mm−2), thermodynamic instability and spatial inhomogeneity. In this paper, we report ultrahigh density (∼109 mm−2) of edge dislocations that are uniformly distributed in oxide ceramics with large compositional complexity. We demonstrate the dislocations are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(48 citation statements)
references
References 52 publications
1
45
1
1
Order By: Relevance
“…Nevertheless, a recent dedicated TEM study has shown an enhanced degree of dislocation densities in pyrochlore‐HEO systems. [ 35 ] Hence, probing of unique and possibly enhanced lattice imperfections might be an interesting research avenue for HEOs in general. In addition, the defects observed here can also have a decisive influence on the properties, for instance, the missing plane (MnO) and the stacking fault‐like feature are likely to impact the MnOMn bonding characteristics that govern exchange interactions in manganites.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a recent dedicated TEM study has shown an enhanced degree of dislocation densities in pyrochlore‐HEO systems. [ 35 ] Hence, probing of unique and possibly enhanced lattice imperfections might be an interesting research avenue for HEOs in general. In addition, the defects observed here can also have a decisive influence on the properties, for instance, the missing plane (MnO) and the stacking fault‐like feature are likely to impact the MnOMn bonding characteristics that govern exchange interactions in manganites.…”
Section: Resultsmentioning
confidence: 99%
“…Materials with increased conguration entropy have attracted broad interest due to their large enhancement in mechanical and thermal properties. 27,28,33,38,39 To investigate the increased-entropy effect in ceramics, we conducted molecular dynamics (MD) simulations with enhanced sampling methods [40][41][42] and machine learning potentials 43 in the unary, binary, ternary, and quaternary material systems (Fig. 1a, and Fig.…”
Section: Medium-entropy Ceramic Designmentioning
confidence: 99%
“…High-entropy oxides (HEOs) are oxide solid solutions with one or more lattice sites occupied by equivalent/near-equivalent atoms of different elements [15]. Normally, the number (N) of elements in one or more lattice sites is greater than four in HEOs, [15,16], RE 3 NbO 7 [3,17], RE 2 Si 2 O 7 [18], and others [1922]. The properties of the aforementioned oxides have been successfully tailored and optimized, and thus the study of HEOs advances the development and application of various materials.…”
Section: Introduction mentioning
confidence: 99%
“…However, weberite-type RE 3 Nb/TaO 7 ceramics had inadequate mechanical properties, e.g., La 3 NbO 7 had hardness, toughness, and Young's modulus of approximately 4.5 GPa, 0.5 MPa•m 1/2 , and 100 GPa, respectively [23]. 7 yttria-stabilized zirconia (7YSZ), La 2 Zr 2 O 7 , and Yb 3 NbO 7 had high hardness (H = 913 GPa) and Young's modulus (E = 200250 GPa), and 7YSZ were widely used as protective coating materials due to their excellent fracture toughness (K IC = 3.5 MPa•m 1/2 ) [2,5,15,16,19]. The fluorite RE 3 Nb/TaO 7 HEOs have been studied to optimize their properties.…”
Section: Introduction mentioning
confidence: 99%
See 1 more Smart Citation